Răspuns :
a-b=80 ⇔ b=a-80
a/2=2*b/2+10 ⇔ a/2=b+10 ⇔ b=a/2-10 ⇒
a-80=a/2 -10
a-a/2 =80-10
a/2=70
a=140
b=140-80=60
a/2=2*b/2+10 ⇔ a/2=b+10 ⇔ b=a/2-10 ⇒
a-80=a/2 -10
a-a/2 =80-10
a/2=70
a=140
b=140-80=60
Fie x si y cele doua numere :
x - y = 80
(x : 2) : (y : 2) = 2 rest 10 ==>
==> conform T.I.R
==> x : 2 = 2 × y : 2 + 10 | ×2
==> x = 2y + 20
inlocuim in prima relatie pe x
2y + 20 - y = 80
y = 80 - 20 = 60
x = 80 + 60 = 140
x - y = 80
(x : 2) : (y : 2) = 2 rest 10 ==>
==> conform T.I.R
==> x : 2 = 2 × y : 2 + 10 | ×2
==> x = 2y + 20
inlocuim in prima relatie pe x
2y + 20 - y = 80
y = 80 - 20 = 60
x = 80 + 60 = 140